Implementasi Permainan Kolase dari Bahan Alam untuk Mengembangkan Motoric Halus Anak Usia Dini - Nurul Khasanah, Elvi; Puspita sari, Ayu; Retno sari, Yosi (JPT : Jurnal Pendidikan Tematik, 2024)
Implementation of collage games from natural materials to develop fine motor skills in early childhood. This research aims to improve children's fine motor skills through collage activities with natural materials in early childhood. This type of research is a literature review. The subject of this research is: articles or journals related to the Implementation of Collage Games from Natural Materials. Data collection techniques use the results of work, observation and documentation of classroom action research (PTK). The procedure in this research has 4 stages, namely planning, carrying out actions, observing or observing and reflecting. Data analyzed in carrying out classroom action research, there are two types used, namely qualitative data and quantitative data, comparing the level of understanding and treatment achieved by children with the indicators applied. The results of the research showed that the improvement in fine motor skills through collage activities with natural materials around each cycle of children's fine motor skills increased from pre-cycle 25.5% in cycle I to 58.3% in cycle II to 83.5% so the conclusion of this research is that the activities Collage of natural materials can improve students' fine motor skills.